Physico-chemical characteristics of butter prepared from the milk of selected indigenous and crossbred cows - Sathiya, Taherabbas; Ramani, Akshay; Seth, Raman; Gandhi, Kamal; Sharma, Rajan; mann, Bimlesh (Indian Journal of Dairy Science, 2024)
This study aimed to investigate the effects of the season in relation to breed and the butter preparation method on chemical composition, β-carotene content, conjugated linoleic acid (CLA) content, color attributes, texture profile, and keeping quality. Fat content showed minor variation in butter types, conventional butter had significantly (p